DETERMINATION OF ANNONACYN COMPOUND BY HIGH PERFORMANCE LIQUID CHROMATOGRAPHY ON THE EXTRACT OF Annona muricata LINN SEED FOR PESTICIDE FORMULA - Freddy L Wurangian (Universitas Gadjah Mada, 2005)
Determination of annonacyn grade, a main insecticide compound has been done in the ethanolic and ethyl acetate extracts produced by soxhletation, and ethyl acetate extract produced by fractionation of ethanolic extract to find out the most active extract to be used as raw material of pesticide formulae. Analysis method used the reverse phase high performance liquid chromatography with column of Novapack ODS C-18 (waters; 3.9 x 150 nm), mobile phase was the mixture of acetonitrile-water. The result of this research showed the optimum condition as follows: the mobile phase was acetonitrile-water (60:40), flow rate of 0.2 mL min-1, injection volume of 5.0 μL, detector UV, wavelength (λ) at 220 nm with AUFS of 1.00. The limit detection of annonacyn was 0.01 μg, annonacyn grade in ethanolic extract produced by soxhletation: 0.0405 + 0.0021%, in ethyl acetate extract produced by soxhletation: 0.0293 + 0.0009%, in ethyl acetate extract produced by fractionation of ethanolic extract: 0.1003 + 0.0018%. The precision and accuracy of annonacyn in this research were respectively obtained 8.89% - 1.92%, and 4.91% - 7.28%, at the concentration of 5.00 μg mL-1 - 25.00 μg mL-1. The sensitivity was 0.75 < b < 1.13.